"Constitutionalism in the Americas": Colin Crawford and Daniel Bonilla Maldonado (eds.) - Segovia, Juan Fernando (Derecho Público Iberoamericano, 2021)
Colin Crawford and Daniel Bonilla Maldonado (eds.), "Constitutionalism in the Americas", Cheltenham/Northampton, Massachusetts, Edward Elgar Publishing Limited, 2018